Corporate Social Responsibility Disclosure and Profitability Against Tax Avoidance in the Jakarta Islamic Index (JII): Corporate Social Responsibility Disclosure dan Profitability Terhadap Tax Avoidance di Jakarta Islamic Index (JII) - Nawangsari, Ajeng (Journal of Accounting Science, 2022)
This study aims to see whether Corporate Social Responsibility Disclosure (CSRD) and Profitability have an effect on Tax Avoidance. This research took place over four years, from 2017 to 2020 and focused on companies listed on the Jakarta Islamic Index (JII). This study has a total sample of 136, with 34 companies per year. STATA software was used to perform multiple linear regression analysis to evaluate the research hypotheses. Based on the conclusion of this study, the variable Corporate Social Responsibility Disclosure (CSRD) has a significant negative effect on Tax Avoidance. On the other hand, Profitability has a significant negative impact on Tax Avoidance. Furthermore, Corporate Social Responsibility Disclosure and Profitability simultaneously affect Tax Avoidance. The results of this study can be used for further research to be able to develop the characteristics of other companies that may have an influence on tax avoidance in addition to the profitability variable. In addition, this research can also be developed using ESG disclosure as an alternative to CSR disclosure in order to observe the differences and their effects on tax avoidance